The Effect Of Product Quality, Brand Image, And Price Perception On The Purchase Decision Of Pt. Indofood Products In The City Of Bengkulu - Wulandari, Annisa; Monique D, Eska Prima; Abi , Yudi Irawan (Jurnal Pusat Manajemen, 2025)
This study aims to analyze the influence of product quality, brand image, and price perception on consumer purchasing decisions for PT. Indofood products in Bengkulu City. Indofood, as one of Indonesia’s largest food manufacturers, faces intense market competition that requires a strong understanding of consumer behavior. Product quality, brand image, and price perception are key factors that shape consumer trust, preferences, and purchasing decisions. Using a quantitative approach with a survey method, questionnaires were distributed to 106 consumers who had purchased Indofood products in Bengkulu City. The collected data were analyzed using multiple linear regression through SPSS version 25.0 to examine the partial and simultaneous effects of the three variables on purchasing decisions. The results of the study show that product quality, brand image, and price perception each have a positive influence on consumer purchasing decisions. This indicates that when consumers perceive a product as high quality, view the brand as strong and trustworthy, and consider the price as fair relative to the benefits received, they are more likely to make a purchase. Overall, this study demonstrates that purchasing decisions are not determined by a single factor but rather by the combined influence of product quality, brand reputation, and perceived value of price. These findings suggest that PT. Indofood should consistently maintain the quality of its products, strengthen its brand image through effective communication strategies, and set prices that reflect both consumer value perceptions and market competitiveness to sustain its position as a leading brand in the food industry.